sCD40 and sCD40L as candidate biomarkers of rheumatic diseases: a systematic review and meta-analysis with meta-regression - Zinellu, Angelo; Mangoni, Arduino A. (Frontiers in Immunology, 2025)
There is an ongoing search for novel biomarkers to enhance diagnosing and monitoring patients with rheumatic diseases (RDs). We conducted a systematic review and meta-analysis to investigate the potential role of the soluble cluster of differentiation 40 (sCD40) and sCD40 ligand (sCD40L), involved in humoral and cellular immune response, as candidate biomarkers of RDs. We searched PubMed, Web of Science, and Scopus from inception to 30 June 2024 for studies investigating circulating sCD40 and sCD40L concentrations in RD patients and healthy controls. We assessed the risk of bias using the Joanna Briggs Institute Critical Appraisal Checklist for analytical studies and the certainty of evidence using the Grades of Recommendation, Assessment, Development and Evaluation Working Group system. Compared to controls, RD patients had significantly higher sCD40L (31 studies; standard mean difference, SMD=0.87, 95% CI 0.60 to 1.13, p<0.001; low certainty of evidence) and sCD40 (five studies; SMD=1.32, 95% CI 0.45 to 2.18, p=0.003; very low certainty of evidence) concentrations. In meta-regression and subgroup analysis, the effect size of the between-group differences in sCD40L was significantly associated with sample size, mean RD duration, specific RD, biological matrix assessed, and analytical method used. By contrast, there were no associations with age, sex, C-reactive protein, erythrocyte sedimentation rate, use of disease-modifying antirheumatic drugs or glucocorticoids, or geographical location. There were no significant differences in sCD40L concentrations between RD patients with and without active disease (eight studies; SMD=0.12, 95% CI -0.09 to 0.33, p=0.26; very low certainty). By contrast, sCD40 concentrations were significantly higher in RD patients with active disease (three studies; SMD=0.36, 95% CI 0.08 to 0.84, p=0.013; very low certainty). Our systematic review and meta-analysis suggests the potential role of sCD40 and sCD40L as candidate biomarkers to detect the presence of RDs (sCD40 and sCD40L) and monitor disease activity (sCD40). Large, appropriately designed prospective studies in a wide range of RDs are warranted to investigate whether measuring sCD40 and sCD40L can significantly improve the performance of currently available diagnostic criteria and serological biomarkers. (PROSPERO registration number: CRD42024577430).Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024577430, identifier PROSPERO CRD42024577430.